Variable phenotypic presentation of iron overload in H63D homozygotes: are genetic modifiers the cause?. Issue 6 (1st June 2001) - Aguilar-Martinez, P; Bismuth, M; Picot, M C; Thelcide, C; Pageaux, G-P; Blanc, F; Blanc, P; Schved, J-F; Larrey, D
Abstract : BACKGROUND: First considered as a polymorphism of the HFE gene, the H63D mutation is now widely recognised as a haemochromatosis associated allele. But few H63D homozygotes with clinical manifestations of hereditary haemochromatosis (HH) have been reported. Concurrently, an increasing number of genes have been shown to interact with HFE in iron metabolism. AIMS: To describe the clinical expression of iron overload (IO) associated with H63D homozygosity, and search for potential genetic modifiers (within the HFE or other genes) that could explain the variability of the phenotypes. PATIENTS AND METHODS: We retrospectively analysed the clinical phenotype of 56 H63D homozygotes referred for a personal or family history of IO. For each subject we examined intragenic HFE haplotypes and transferrin receptor (TfR) gene polymorphisms and searched for the Y250X mutation on the TFR2 gene. Additionally, we sequenced the HFE gene of H63D homozygotes with HH. RESULTS: Fifty of 56 subjects had biological and/or clinical abnormalities of iron metabolism. Up to two thirds of patients (n=34) had no acquired cause of IO. Among these, 12 had a phenotypic diagnosis of HH. In the iron loaded group there was a strong prevalence of male patients. No correlation was found between the potential genetic modifiers and phenotypes. No additional mutation of HFE was identified. CONCLUSION: The variable phenotypes associated with H63D homozygosity do not appear to be linked to other HFE mutations, to the TFR2 Y250X mutation, or to HFE or TfR gene intragenic polymorphisms. The exact role of H63D homozygosity in IO and HH needs to be further investigated in unselected populations.